Brief history of the Citizens Education Committee of La Crosse, Wisconsin, 1961-1968 - Kritchman, Ruth Bires (My University, 1969)
Statement of the problem. The purpose of this paper was to describe the activities and accomplishments of the Citizens Education Committee of La Crosse, Wisconsin from its origin in 1961 to 1968 and establish its influence on the educational policies of the La Crosse Public Schools. Method and procedure used. The primary source of information for this paper was the records kept by the secretaries of the Citizens Education Committee. Newspaper articles relating to the subject were checked on microfilmed copies of the La Crosse Tribune at the La Crosse Public Library. Books used in the preparation of this paper were obtained from the Murphy Library at Wisconsin State University-La Crosse and La Crosse Public Library. Telephone calls were made to ten members of the Citizens Education Committee who had been consistently active in the organization to seek their cooperation in answering questionnaires. Information secured from the questionnaires was used directly or indirectly in the preparation of this paper. Summary of the findings. The Citizens Education Committee began as a study group concerned about public education in La Crosse. The members invested much time and study into identifying educational problems in the schools and working toward solutions. Due to their public relations work, the community became more aware of the school situation. Political pressures by the Citizens Education Committee helped provide qualified candidates for the Common Council as well as the school board. The change from a school board selected by the Common Council to one elected by the voters is the single contribution of the Citizens Education Committee which establishes their influence on the policies of the La Crosse Public Schools.
Keywords: Citizens Education Committee of La Crosse (Wis.); School boards -- Law and legislation -- Wisconsin -- La Crosse; Education -- Wisconsin -- La Crosse